Analysis of the Implementation of Health Worker Competency Development - Hery Pranoto; Saimi Saimi; Sismulyanto Sismulyanto (Indonesian Journal of Global Health Research, 2025)
The suboptimal competency development program for healthcare workers in regional general hospitals affects the fulfillment of professional competency requirements and integration as a superior, international-class referral hospital chosen by the community with excellent and comprehensive services. This study aims to explore the implementation of the healthcare worker competency development program through input, process, and output, as well as identifying problems encountered and solutions to overcome them at the NTB Provincial Hospital. This study uses a Qualitative Descriptive approach using the Donabedian framework (input, process, and output) with in-depth interviews, observation, and document analysis methods. The informants numbered 14 people, determined by purposive sampling, namely selecting several health workers who have experience, strategic positions, or perspectives that are considered capable of providing in-depth insights regarding training needs. Data analysis used the interactive model of Miles and Huberman involving data collection, data reduction, data presentation, and drawing conclusions. This study found that the implementation of healthcare worker competency development has been running normatively, but there are problems with the lack of number and type of competency development and its uneven distribution. The large number of employees, types of health workers and the many varied service units demand a very important need in the development of health worker competencies, problems with the Training Needs Assessment (TNA) have not been carried out properly, implementing personnel or training organizers who have not been trained, lack of infrastructure for certain specific training and limited budgets, and there is no binding policy to implement SPM 20JP. The development of health worker competencies at the NTB Provincial Hospital has not reached an optimal level due to limited budget allocations, the large number of personnel accompanied by the diversity of types of services that require must be a priority agenda because of the importance of equitable and planned competency development to ensure the quality, effectiveness, and sustainability of health services.